THE EFFECT OF PRICES AND PROMOTIONS ON PURCHASE DECISIONS AT SHOPEE: CASE STUDY OF BHAYANGKARA UNIVERSITY JAKARTA RAYA - Matdio Siahaan; Dian Christiani (International Journal of Economy, Education and Entrepreneurship, 2021)
This study was conducted to determine and understand the relationship between the independent promotion variables and price on the dependent variable purchasing decisions. The research was carried out at Bhayangkara University, Greater Jakarta. More precisely, at the Faculty of Economics and Business with an associative approach. The technique used is a purposive sampling; this research was carried out by distributing online to students at Bhayangkara University, especially the Faculty of Economics and Business, obtained 120 samples from the survey conducted and then processed using SPSS version 25. The data became primary data, and the results obtained that the Promotion variable partially affects the Purchase Decision variable by -1,396. The Promotional Variable simultaneously affects the Purchase Decision variable by 89,386